THE IMPLEMENTATION OF LEGAL RISK MANAGEMENT IN COMPANIES RELATED TO EARNINGS MANAGEMENT OF MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Dompak Pasaribu; Silvia Shania Sinaga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study adopts a socio-legal approach, which is a non-doctrinal method in legal research, to explore the role of Directors in implementing legal risk management and earnings management post-COVID-19 pandemic. The research method integrates various disciplines to gather empirical data needed to address research questions focused on practical issues, policies, and legal changes. This non-doctrinal research combines qualitative and quantitative aspects using empirical data to analyze the impact of effective legal risk management on the financial performance and reputation of manufacturing companies in the consumer goods industry sector during the COVID-19 pandemic. Through comprehensive empirical data collection, this study aims to provide an in-depth understanding of the role of Directors in managing legal risks and earnings management and their impact on the financial performance and reputation of companies during the pandemic crisis. Findings from this research are expected to provide valuable insights for legal practitioners, corporate management, and researchers to develop effective strategies in addressing challenges faced by manufacturing companies in the consumer goods industry sector during the COVID-19 pandemic.